2022
DOI: 10.3389/fonc.2022.817584
|View full text |Cite
|
Sign up to set email alerts
|

Mutant NPM1-Regulated FTO-Mediated m6A Demethylation Promotes Leukemic Cell Survival via PDGFRB/ERK Signaling Axis

Abstract: Acute myeloid leukemia (AML) with nucleophosmin 1 (NPM1) mutations exhibits distinct biological and clinical features, accounting for approximately one-third of AML. Recently, the N6-methyladenosine (m6A) RNA modification has emerged as a new epigenetic modification to contribute to tumorigenesis and development. However, there is limited knowledge on the role of m6A modifications in NPM1-mutated AML. In this study, the decreased m6A level was first detected and high expression of fat mass and obesity-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…Nevertheless, based on the fact that NPM1 mutants cannot directly regulate gene transcription [ 29 ], we deduced that other molecular events participate in the regulation of TP53INP2 transcripts. Considering our recent studies showed that NPM1-mA can stabilize m 6 A demethylase FTO to participate in the transcriptional regulation of target genes [ 30 ], we investigated whether FTO-mediated demethylation regulates the expression of TP53INP2 . Initially, several m 6 A methylated sites in the TP53INP2 mRNA were identified using the sequence-based RNA adenosine methylation site predictor (SRAMP) ( Figure 3 E).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, based on the fact that NPM1 mutants cannot directly regulate gene transcription [ 29 ], we deduced that other molecular events participate in the regulation of TP53INP2 transcripts. Considering our recent studies showed that NPM1-mA can stabilize m 6 A demethylase FTO to participate in the transcriptional regulation of target genes [ 30 ], we investigated whether FTO-mediated demethylation regulates the expression of TP53INP2 . Initially, several m 6 A methylated sites in the TP53INP2 mRNA were identified using the sequence-based RNA adenosine methylation site predictor (SRAMP) ( Figure 3 E).…”
Section: Resultsmentioning
confidence: 99%
“…Initially, we revealed that knockdown and overexpression of NPM1-mA affected the level of TP53INP2 transcripts. Considering NPM1-mA cannot directly regulate the transcription of target genes [ 29 ] but NPM1-mA can stabilize demethylase FTO to participate in transcriptional regulation [ 30 ], we investigated whether FTO-mediated demethylation modulates TP53INP2 expression. Then, the binding of TP53INP2 mRNA and FTO was confirmed by RIP experiments.…”
Section: Discussionmentioning
confidence: 99%
“…A novel developed N6‐methyladenosine demethylase FTO small‐molecule inhibitor 18097 with a potent (IC 50 values 0.64 μmol/L) showed the suppressive effects on cell growth and lipogenesis in breast cancer cells 155 . Besides, recently, several small‐molecule compounds such as meclofenamate sodium, 156 FB23, 157 FB23‐2, 158 Dac51, 158 and bisantrene were reported to exhibit high efficacy of FTO inhibition 159 . However, whether these molecules improve the function, identity, and mass of β‐cell and IR in vivo and in vitro still warrants further investigation.…”
Section: M6a In Dm Diagnosis and Therapymentioning
confidence: 99%
“…In GBM, the SPI1-induced downregulation of FTO promotes tumor progression by regulating pri-miR-10a processing in an m6A-dependent manner 66 . In contrast, for NPM1-mutated AML, which accounts for approximately one-third of AML cases, FTO is aberrantly overexpressed and serves as a carcinogen by promoting the cell cycle and inhibiting apoptosis 67 . Similarly, ALKBH5 promotes tumor growth and metastasis through the TRAF1-mediated activation of the NF-κB and MAPK signaling pathways in multiple myeloma 68 .…”
Section: The Double Sword Of M6a In Human Cancersmentioning
confidence: 99%